LABORATORY STUDIES OF THE EFFECT OF THE ELECTRIC FIELD STRENGTH ON THE SPECIFIC CHARGE ON REAGENT PARTICLES FORMED DURING THE SUBLIMATION OF PYROTECHNIC COMPOSITIONS - B. Khuchunaev; S. Gekkieva; A. K. Budaev (Наука. Инновации. Технологии, 2022)
Introduction. Until now, despite the fact that reagents have long been used to control cloudy processes, issues related to the influence of an electric field on their ice-forming properties have not been fully studied. Studies carried out in this direction show that the growth of seed particles depends on the electric field strength, the charge of the crystallizing nucleus, and on the implementation of one or another growth mechanism [1]. The presence of an electric ield and a charge on the reagent particles in the atmosphere can affect the specific yield of ice-forming nuclei during work on active action on cloud systems. In this regard, studies related to the study of the effect of the electric ield strength on the speciic charge on the reagent particles formed during the sublimation of pyrotechnic compositions seem relevant and practically significant for determining the dosage of reagents when exposed to cloudy processes. Materials and methods of the research. This article presents the results of laboratory experiments on testing the equipment and methods for determining the effect of the electric field strength on the speciic charge on the reagent particles formed during the sublimation of pyrotechnic compositions. The method for measuring charged particles is based on the use of the delection of reagent particles in the electric field of a flat capacitor. The preliminary results obtained in the course of research made it possible to establish that the particles are charged during the sublimation of pyrotechnic compositions. pyrotechnic compositions used in anti-hail devices such as «Alazan-6» and «Alazan-9» [2, 3, 4] were considered as a working material for laboratory research. The results of the study and their discussion. The article presents the equipment, methodology and preliminary results of the study of the inluence of the electric ield strength on the speciic charge on the reagent particles formed during the sublimation of pyrotechnic compositions. Laboratory experiments were carried out on High-Mountain Geophysical Institute laboratory facilities. Conclusions. The experiments have shown that an increase in the negative speciic charge on the reagent particles slightly increases the speciic yield of ice-forming nuclei (by 20%) from the AD-1 pyrotechnic composition. With an electric field strength of -8,4 х 10-4 V/m and a specific charge on the reagent particles of 3,0 х 105 C/kg, the specific yield of ice-forming nuclei from the AD-1 pyrotechnic composition is 2.7 times higher than without an electric ield